4×4 Knight’s Graph Analysis by Modularity A Knight Graph Application - Güldal, Serkan (Fırat University, 2021)
Modularity is a well-known technic to analyze graphs of datasets. The modularity divides the network into meaningful clusters. The clusters present the existence of shared properties between the nodes in the same cluster. In the present study, we analyze 4×4 knight graph by modularity to investigate 4-KCP solutions. Our investigation is completed for resolutions from 0.2 to 3.2. The maximum modularity score is 0.417 found (for resolution = 0.6, 0.8, 1, and 1.4). Moreover, resolution 1.4 is the optimum resolution to find some solutions of 4-KCP. Also, the analyses show resolution 0.2 is the best resolution to find all solutions of 4-KCP.
Keywords: Engineering; Mühendislik